2009
DOI: 10.1088/0957-0233/20/7/075405
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the transient mass flow rate in a simplex swirl injector

Abstract: When a heat release and acoustic pressure fluctuations are generated in a combustor by irregular and local combustions, these fluctuations affect the mass flow rate of the propellants injected through the injectors. In addition, variations of the mass flow rate caused by these fluctuations bring about irregular combustion, which is associated with combustion instability, so it is very important to identify a mass variation through the pressure fluctuation on the injector and to investigate its transfer functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…With respect to the signal processing circuit, it is reported that an alternating current (AC) power supply is preferred to a direct current power supply because the current does not flow well if polarization occurs [7]; therefore, in this study, AC excitation of 20 kHz was adopted. Although the form of the electrodes is similar to many other researchers' [5,7,8,10,13], the measurement circuit is unique in the present study. Because the pulsation of liquid film is very small, and always accompanied by considerable noise, the lock-in amplifier was used in the signal processing circuit; because of its ability to suppress noise, it is widely used to detect weak signals.…”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…With respect to the signal processing circuit, it is reported that an alternating current (AC) power supply is preferred to a direct current power supply because the current does not flow well if polarization occurs [7]; therefore, in this study, AC excitation of 20 kHz was adopted. Although the form of the electrodes is similar to many other researchers' [5,7,8,10,13], the measurement circuit is unique in the present study. Because the pulsation of liquid film is very small, and always accompanied by considerable noise, the lock-in amplifier was used in the signal processing circuit; because of its ability to suppress noise, it is widely used to detect weak signals.…”
Section: Methodsmentioning
confidence: 86%
“…When heat release and acoustic pressure fluctuations are generated in a combustor, these fluctuations affect the flow rate of the propellants injected through the injectors. In addition, variations of the flow rate caused by these fluctuations bring about irregular combustion, which is associated with combustion instability, so it is very important to determine whether a flow rate variation is caused by pressure fluctuation in the injector and to investigate its transfer function [8]. The aim of an investigation of injector dynamics is to understand the response of the volume flow of the injector to the pressure fluctuations [9].…”
mentioning
confidence: 99%
“…The pressure in the orifice and liquid film thickness were measured during the experiment and mass flow rate through the orifice was calculated using DPMM with the data obtained above (Khil et al, 2009). …”
Section: Methodsmentioning
confidence: 99%
“…The discharge coefficient μ, which plays a dominant role in determining the mass flow rate, was calculated as follows (Borodin et al, 1967;Kulagin and Moroshkin, 1966). (n: number of tagnential entries)…”
Section: Mass Flow Ratementioning
confidence: 99%
See 1 more Smart Citation